The Relationship of Physical Activity with the Level of Colon Cleanliness in Colonoscopy Patients at the Gastrointestinal Endoscopy Center - Manurung, Sondang Tio Helena; Lukmana, Sorich; Setiyadi, Agung; Wardani, Nuniek Setyo (Indonesian Journal of Global Health Research, 2024)
Colonoscopy is an examination of the colorectum and terminal ileum which is carried out by inserting a scope with a camera and a flexible light source through the anus. Colons that are still dirty or not clean, up to 20-30% of colonoscopies are reported to be canceled or rescheduled. The muscle tone of the abdomen, pelvis and diaphragm is influenced by physical activity which facilitates defecation. The aim of the study was to determine the relationship between physical activity which influences the level of colonic cleanliness in colonoscopy patients. The study involved 75 subjects who underwent colonoscopy procedure in November-December 2023 using the WHO GPAQ 2016 questionnaires and Boston Bowel Preparation Scale (BBPS). The design uses quantitative descriptive methods with cross sectional analysis. The data obtained was then subjected to statistical tests using SPSS chi-square. The test results obtained a p-value of 0.005 (p < 0.05). The results of this study indicate that there is a significant relationship between physical activity and colon cleanliness.